Educational Needs Assessment of Managing Directors of Rural Cooperatives in Mazandaran Province in the Field of Entrepreneurship Management - Amir Ahmadpour; Najibeh Nour Mohammadi; Hadi Moumeni Helali; Jamileh Aliloo (تعاون و کشاورزی, 2020)
The aim of this study was to identify the educational needs of managingdirectors of rural cooperatives in the field of entrepreneurship management bysurvey method. The statistical population of the study consisted of themanaging directors of rural cooperatives and training experts of cooperativeoffices in Mazandaran province. A total of 183 managing directors ofcooperatives and 54 experts of cooperative offices in Mazandaran provincewere surveyed by census method. The face and content validity of the researchtool was confirmed by experts and professors in the field of entrepreneurship.The reliability of the research instrument was confirmed using Cronbach's alphain the range (0.77 to 0.98). This research was conducted in two stages: first, theeducational needs of managing directors were determined from their own pointof view and then from the point of view of experts using a questionnaire basedon the Burich model. In the second stage, in order to determine the level ofagreement between the managing directors of cooperatives and expertsregarding their educational needs, the quadrant model was used. The resultsshowed that the dimensions of financial management and strategic managementwere identified as priority training needs of managing directors of ruralcooperatives in the field of entrepreneurial management and were prioritized intraining programs. It is necessary to provide theoretical and practical training inaccordance with the priorities in accordance with each need in order toultimately promote the entrepreneurial management characteristics of themanaging directors and provide the ground for the growth and development ofcooperatives in the market.